Body mass index and waist-to-height ratio among schoolchildren with visual impairment: A cross-sectional study. Issue 32 (August 2016) - Magdalena, Wrzesińska; Urzędowicz, Beata; Motylewski, Sławomir; Zeman, Krzysztof; Pawlicki, Lucjan
Abstract : Abstract: Children and adolescents with visual impairments may be predisposed to excessive body mass due to restrictions in everyday functioning and the ability to take part in physical activity. This study aimed to estimate the prevalence of obesity, overweight, and abdominal obesity (AO) among blind and partially sighted schoolchildren and to determine whether sociodemographic factors and participation in physical education classes (PEC) are associated with excessive body weight or AO in this group. A cross-sectional sample of 141 partially sighted or blind schoolchildren aged 7 to 18.9 years were included in this study. Anthropometric measurements were performed, and sociodemographic variables and ability to attend PEC were recorded. Overweight and obesity were noted among 21.3% and 14.9% of students, respectively. Although more males than females had excessive body weight (39.2% vs 32.3%), the difference was not significant (chi square test [ch 2 ] = 3.197; probability value [ P ] = 0.362). There was a significant association between mean body mass index standard deviation score and age (results of ANOVA analysis [ F ] = 5.620; P  = 0.0045). A waist-to-height ratio (WHtR) ≥0.50 was observed among 27.7% of pupils. The prevalence of AO in boys and girls was 32.9% and 21.0%, respectively; this difference was not significant (ch 2  = 2.48; P  = 0.12). There was a significant relationship between mean WHtR and age (7–9 years: 0.477 ± 0.050; 10–13 years: 0.484 ± 0.065; ≥14 years: 0.454 ± 0.061; results of Kruskal–Wallis test [ H ] = 8.729; P  = 0.023, respectively). Multivariate logistic regression analysis showed that none of the sociodemographic variables examined (except "having siblings") were significantly associated with the occurrence of overweight, obesity, and AO. Subjects with no siblings were 4 times more likely to have WHtR ≥ 0.5 (odds ratio [OR] = 4.22; 95% confidence interval [CI] = 1.33–17.8; P  = 0.01). Overweight and obesity were almost 4 times more frequent (OR = 3.74; 95% CI 0.81–17.4) and AO 3 times more frequent (OR = 3.18, 95% CI 0.71–14.2) among students not participating in PEC. Excessive body mass and AO represent an urgent health problem among schoolchildren with visual impairments. Health education concerning healthy eating habits and physical activity should be provided to this group to reduce potential future health costs.